Assessing Startup Performance: "Case Study at National Business Incubator" - Mayar Soeryo Prayogo; Usep Suhud; Agung Wahyu Handaru (International Journal on Advanced Science, Education, and Religion, 2019)
This study aims to examine the Startup Performance of the national incubator which are includes Knowledge Management, Business Incubator, and the effectiveness of innovation. Besides that this research is expected to have tangible benefits toward the process of achieving Startup goals that owned by business performers. This study will test five hypotheses of direct influence (effect) and two hypotheses of mediating influence (indirect effect). This study will use 339 respondents as sample with a Startup analysis unit that operates and is affiliated with a local Startup development business incubator located in Jabodetabek, West Java Province (excluding Depok & Bekasi), Central Java and Bali. The intended startup on this research is Person In Charge (PIC) / company founder / owner. The PIC / founder / owner of the company here is not limited by age, gender and position at the Startup. The company's PIC / founder / owner is only limited towardStartup which is built by the business incubator. The research method used is Confirmatory Factor Analysis (CFA) to test path analysis by operating AMOS 22. The results of this study indicate that all proposed hypotheses can be accepted statistically, both direct side and indirect effects (mediation) side